Perancangan Sistem Produksi Lampu dengan Metode Perancangan Berorientasi Objek di PT. Cosmo Technology Indonesia Kabupaten Sukabumi - Wawang Adi darma (JURNAL BUANA INFORMATIKA CBI, 2017)
The development of information technology (IT) so rapidly, including for the field of ERP (Enterprice Resources Planning). To design and build an ERP system, it is necessary to first analyze the system to be built, especially for the design of Rekayas Software (RPL). The results of this study are expected to find the results of good and correct analysis so as to be able to implement the system into a program using JAVA. This research consists of several parts analysis. The core of this research is to review the problems that exist in the company, in determining user requirements or user needs, then generate design in the form of diagrams used as a system design tool. The point explanation that will be done is Business Overview, Organizational Structure, Department Description, User Requirement. While the design of the system using UML consisting of several diagrams are Activity Diagram, Use Case Diagram, Sequence Diagram, Class Diagrams, Entity Diagrams, Communication diagrams, State Machine Diagrams, Component Diagrams, Deployment Diagrams, Composite Structure Diagrams, Interaction Overview Diagrams, Object Diagrams , Package Diagram, Timing Diagram, The author takes the object case that is PT. COSMO TECHNOLOGY which is located at Jl. Raya Segog Km.14 Batununggal Village Kec. Cibadak, Sukabumi-West Java. Is a company engaged in decorative lights and is developing a business in the field of toys. Keywords: ERP, UML